Outcomes in Octogenarians and the Effect of Comorbidities After Intact Abdominal Aortic Aneurysm Repair in the Netherlands: A Nationwide Cohort Study. (June 2021) - Alberga, Anna J.; Karthaus, Eleonora G.; van Zwet, Erik W.; de Bruin, Jorg L.; van Herwaarden, Joost A.; Wever, Jan J.; Verhagen, Hence J.M.; ,; ,; ,; Van den Akker, P.J.; Akkersdijk, G.J.; et al.
Abstract : Objective: Age is an independent risk factor for mortality after both elective open surgical repair (OSR) and endovascular aneurysm repair (EVAR). As a result of an ageing population, and the less invasive nature of EVAR, the number of patients over 80 years (octogenarians) being treated is increasing. The mortality and morbidity following aneurysm surgery are increased for octogenarians. However, the mortality for octogenarians who have either low or high peri-operative risks remains unclear. The aim of this study was to provide peri-operative outcomes of octogenarians vs. non-octogenarians after OSR and EVAR for intact aneurysms, including separate subanalyses for elective and urgent intact repair, based on a nationwide cohort. Furthermore, the influence of comorbidities on peri-operative mortality was examined. Methods: All patients registered in the Dutch Surgical Aneurysm Audit (DSAA) undergoing intact AAA repair between 2013 and 2018, were included. Patient characteristics and peri-operative outcomes (peri-operative mortality, and major complications) of octogenarians vs. non-octogenarians for both OSR and EVAR were compared using descriptive statistics. Multivariable logistic regression analyses were used to examine whether age and the presence of cardiac, pulmonary, or renal comorbidities were associated with mortality. Results: This study included 12 054 EVAR patients (3 015 octogenarians), and 3 815 OSR patients (425 octogenarians). Octogenarians in both the EVAR and OSR treatment groups were more often female and had more comorbidities. In both treatment groups, octogenarians had significantly higher mortality rates following intact repair as well as higher major complication rates. Mortality rates of octogenarians were 1.9% after EVAR and 11.8% after OSR. Age ≥ 80 and presence of cardiac, pulmonary, and renal comorbidities were associated with mortality after EVAR and OSR. Conclusion: Because of the high peri-operative mortality rates of octogenarians, awareness of the presence of comorbidities is essential in the decision making process before offering aneurysm repair to this cohort, especially when OSR is considered.